Mnemonics: an alternative memory enhancement technique in teaching accounting theories / Nor Kartini Mohd Rodzi ... [et al.] - Mohd Rodzi, Nor Kartini; Abdul Rahman, Norshimah; Naiimi, Nazirah; Ahmad @Muhammad, Norizam; Ayob, Susilawani; Selamat, Salwana (Universiti Teknologi MARA, Perlis, 2021)
It is a belief that mnemonic will increase students' understanding and thus, foster their academic performance. This study investigated the effectiveness of using mnemonics in teaching accounting theories for an intermediate financial accounting course. A sample of 96 accounting students enrolling the financial reporting course was chosen to take part in this study. The selected students were separated into 2 groups: M1 was with mnemonic training and M0 was without mnemonic training. The findings revealed that mnemonic is an effective technique in teaching accounting theories and enhancing student's ability to envisage and remember accounting concepts and theories. This is rein-forced from finding that the average score index for students with mnemonic training was 4.985 high-er than those without mnemonic training. In addition, the p-value for the dummy variable mnemonic training (p=.000) was very significant, suggesting that there was statistical evidence of a difference in average score index between the students with a mnemonic and no mnemonic training.